Handbook of strategies and strategic processing - Dinsmore, Daniel L.; Fryer, Luke K.; Parkinson, Meghan M. (Educational psychology handbook series., 2020)
"Handbook of Strategies and Strategic Processing provides a state-of-the-art synthesis of conceptual, measurement, and analytical issues regarding learning strategies and strategic processing. Contributions by educational psychology experts present the clearest yet definition of this essential and quickly evolving component of numerous theoretical frameworks that operate across academic domains. This volume addresses the most current research and theory on the nature of strategies and performance, mechanisms for unearthing individuals' strategic behaviors, and both long-established and emerging techniques for data analysis and interpretation"--